Stimuli-responsive biodegradable polyurethane nano-constructs as a potential triggered drug delivery vehicle for cancer therapy - Gajbhiye, Kavita R.; Chaudhari, Bhushan P.; Pokharkar, Varsha B.; Pawar, Atmaram; Gajbhiye, Virendra (International Journal of Pharmaceutics, 2020)
Polyurethanes (PUs) constitute an essential class of stimuli-responsive and biodegradable material, which has significantly contributed to the advancement of polymers utilization in the biomedical field. The bio-erodible PUs construct an active corridor for facilitating drug into tumor cells, which has significantly impacted the progression of nano-micellar delivery systems. The self-assembled colloidal PUs pose distinctive features such as enhancing the solubility of hydrophobic chemotherapeutics, rapid cellular uptake, triggered erosion and drug release, bio-stimulus sensitivity, improvement in the targeting and proficiency of bioactive. Cationic PUs can easily be condensed with genetic material to form polyplexes and have shown excellent transfection efficiency for potential gene therapy against various cancers. Their modifiable chemistry offers a tool to impart the desired multifunctionality such as biocompatibility, sensitivity to pH, redox, temperature, enzyme, etc. and ligand conjugation for active targeting. These diverse exceptional properties make them excellent nano-carrier for a variety of bioactive, including chemotherapeutic drugs, DNA, RNA, and diagnostic moieties to the target tissue or cells. The PUs based nano-devices have certainly uncovered the path to achieve ideal systems for controlled personalized therapy. The literature discussed in this review shed light on the research innovations carried out in the last ten years for the development of multifunctional PUs for triggered delivery of bioactive to treat various cancers.
Keywords: Cancer nanomedicine; GSH; micelles; Polyurathanes; redox; Stimuli-responsive

Aptamer tethered bio-responsive mesoporous silica nanoparticles for efficient targeted delivery of paclitaxel to treat ovarian cancer cells - Salve, Rajesh; Kumar, Pramod; Chaudhari, Bhushan P.; Gajbhiye, Virendra (Journal of Pharmaceutical Sciences, 2023)
Ovarian cancer is the leading cause of cancer deaths in female patients. The current therapeutics in ovarian cancer are limited and inefficient in curing the disease. To tackle this, we have synthesized tetrasulfide deriv-ative of silica doped, biodegradable, glutathione-responsive targeted mesoporous silica nanoparticles modi-fied with heterobifunctional polyethylene glycol as a linker and mucin-1 aptamer for triggered paclitaxel delivery to the ovarian cancer cells. Degradable mesoporous silica nanoparticles were synthesized by a modi-fied sol-gel method with tetraethyl orthosilicate and Bis (triethoxysilylpropyl) tetrasulfide. The degradable mesoporous silica nanoparticles were characterized by dynamic light scattering, Fourier-transform infrared spectroscopy, Scanning electron microscopy and Transmission electron microscopy. The degradable mesopo-rous silica nanoparticles had good paclitaxel encapsulation efficiency and glutathione-responsive paclitaxel release ability. The glutathione utilization assay and visual destruction observed within 10 days in transmis-sion electron microscopy images confirmed the degradation of the mesoporous silica nanoparticles in the tumor cell environment. The targeted degradable mesoporous silica nanoparticles were efficiently taken up by ovarian cancer cell lines OVACAR-3 and PA-1. The cytotoxicity of bare mesoporous silica nanoparticles evaluated on NIH-3T3 cell line showed good biocompatibility (>90% cell viability). Significant toxicity on OVACAR-3 (IC50 25.66 nM) and PA-1 (IC50 42.93 nM) cell lines was observed when treated with paclitaxel-loaded targeted degradable mesoporous silica nanoparticles. Results of this study demonstrated that mucin-1 targeted, glutathione-responsive mesoporous silica nanoparticles loaded with paclitaxel had a significant antitumor effect on ovarian cancer cells. All these findings demonstrated that developed nano-formulation could be suitable for ovarian cancer treatment. & COPY; 2023 American Pharmacists Association. Published by Elsevier Inc. All rights reserved.
Keywords: Degradable; GSH; Mesoporous silica nanoparticles; Mucin-1; Ovarian cancer; Paclitaxel; Stimuli-responsive

`Turning on' to glutathione: a rhodamine-based fluorescent chemodosimeter with nanomolar sensitivity - Badekar, Pooja S.; Deo, Harshada S.; Varma, Mokshada E.; Kulkarni, Prasad P.; Maibam, Ashakiran; Krishnamurty, Sailaja; Kumbhar, Anupa A. (ChemistrySelect, 2024)
A new colorimetric and fluorescence turn-on chemodosimeter for selective detection of GSH over Cys and Hcy with 34-fold enhancement in emission intensity is reported. Probe 1 exhibited ultra-sensitivity toward GSH with 0.125 nM detection limit and successfully displayed GSH detection in MCF-7 live cells. The mechanism of sensing is established by density functional theoretical calculations.
Keywords: Chemodosimeter; Fluorescence turn-on; GSH; MCF-7 cells; Rhodamine